Pernikahan Masyarakat Muslim Jawa di Bandar Setia - Nasution, Abdul Gani Jamora; Sitompul, Buti Sarma; Daulay, Fitri Ana; Juhaidi, M. Dzaky Labib; Nasution, Nurul Fadilah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Marriage is a marriage ceremony celebrated or carried out by two people with the aim of formalizing the marriage bond in accordance with religious, legal and social norms. There are many types and variations of wedding ceremonies, depending on ethnic traditions, religion, culture and social class. Marriage for Javanese people is considered very sacred, and they only get married once in their life. This purity is the background to the practice of marriage in the Javanese Muslim community which is carried out very effectively and carefully in selecting prospective sons-in-law and determining the right time for marriage. To be precise, the people in Bandar Setia village, Percut Sei Tuan District, Deli Serdang Regency are predominantly Muslim and Javanese. They still uphold Javanese cultural values in the wedding procession. The purpose of this article is to review the Javanese Muslim Community Marriage in Bandar Setia Village. This research method uses qualitative descriptive research. Using observation, interviews and documentation. From the results of this research, the author found two results of discussion, firstly the implementation of marriages in the Javanese Muslim community using the Ngidak Tigan tradition, secondly the meaning of marriage in the Ngidak Tigan tradition according to the understanding of the loyal bandar community.